A clinical procedures curriculum for undergraduate medical students: the eight-year history of a third-year immersive experience. Issue 1 (1st January 2016) - Thompson, Laura; Exline, Matthew; Leung, Cynthia G.; Way, David P.; Clinchot, Daniel; Bahner, David P.; Khandelwal, Sorabh
Abstract : Background: Procedural skills training is a critical component of medical education, but is often lacking in standard clinical curricula. We describe a unique immersive procedural skills curriculum for medical students, designed and taught primarily by emergency medicine faculty at The Ohio State University College of Medicine. Objectives: The primary educational objective of this program was to formally introduce medical students to clinical procedures thought to be important for success in residency. The immersion strategy (teaching numerous procedures over a 7-day period) was intended to complement the student's education on third-year core clinical clerkships. Program design: The course introduced 27 skills over 7 days. Teaching and learning methods included lecture, prereading, videos, task trainers, peer teaching, and procedures practice on cadavers. In year 4 of the program, a peer-team teaching model was adopted. We analyzed program evaluation data over time. Impact: Students valued the selection of procedures covered by the course and felt that it helped prepare them for residency (97%). The highest rated activities were the cadaver lab and the advanced cardiac life support (97 and 93% positive endorsement, respectively). Lectures were less well received (73% positive endorsement), but improved over time. The transition to peer-team teaching resulted in improved student ratings of course activities ( p <0.001). Conclusion: A dedicated procedural skills curriculum successfully supplemented the training medical students received in the clinical setting. Students appreciated hands-on activities and practice. The peer-teaching model improved course evaluations by students, which implies that this was an effective teaching method for adult learners. This course was recently expanded and restructured to place the learning closer to the clinical settings in which skills are applied.